Association between hyperuricemia and clinical pathological characteristics of patients with IgA nephropathy - Ling Lu; Bin Li; Guohua Dai; Yi Feng; Huaguo Feng (Journal of the Pakistan Medical Association, 2021)
Published in August 2021